The Effectiveness of Online Mathematics Subject Learning During the Covid-19 Pandemic at SD Muhammadiyah 49 Jakarta - Siti Masyitoh; Muhib Rosyidi (Jurnal Paedagogy, 2022)
This study aims to analyze the effectiveness of online mathematics subject learning during covid-19. This study used a mixed method with the fifth-graders of SD Muhammadiyah 49 Jakarta Pusat as the study's subjects. This study used observation, questionnaires via a Google form, and interviews as the data collection technique. The data analysis technique used descriptive analysis. The study's results showed that online learning had been effective as seen from the learning process, and the learning objectives that have been achieved. The learning process was running effectively, as seen from several aspects, including the learning process using learning media and seeing interactions between students and teachers. Then, from the outcome aspects, including the achievements made after the learning process, such as the level of student's comprehension.